Perinatal mortality attributable to complications of childbirth in Matlab, Bangladesh - T. Kusiako; C. Ronsmans; L. Van der Paal (The World Health Organization, 2000)
Very few population-based studies of perinatal mortality in developing countries have examined the role of intrapartum risk factors. In the present study, the proportion of perinatal deaths that are attributable to complications during childbirth in Matlab, Bangladesh, was assessed using community-based data from a home-based programme led by professional midwives between 1987 and 1993. Complications during labour and delivery - such as prolonged or obstructed labour, abnormal fetal position, and hypertensive diseases of pregnancy - increased the risk of perinatal mortality fivefold and accounted for 30% of perinatal deaths. Premature labour, which occurred in 20% of pregnancies, accounted for 27% of perinatal mortality. Better care by qualified staff during delivery and improved care of newborns should substantially reduce perinatal mortality in this study population.